Pengaruh Teknik Hypnobirthing terhadap Penurunan Tingkat Nyeri Pada Persalinan : Literatur Review - Siti Qomariyah Ulfah; Yusri Dwi Lestari (Universitas Pahlawan Tuanku Tambusai, 2023)
Childbirth is a natural process that occurs in women with pain caused by uterine contractions. The high pain rate reaches 90% of mothers who give birth. Various actions and efforts have been made to reduce and reduce the level of pain in mothers, one of which is the hypnobirthing method. The purpose of this literature is to identify the effect of hypnobirthing on reducing pain levels in labor. This writer uses the method used in searching for articles is a literature review using the Google Scholar database, Science Direct, and Mendeley. The results of the article search were 654 articles identified from the database. After the screening process left 13 articles that could be assessed for feasibility. 3 out of 13 articles were excluded for some reason, leaving 10 articles to be included. The conclusion from this literature is that hypnobirthing has an effect on reducing pain levels in labor.